Victimological Review of the Impact of Bullying and Legal Protection for Child Victims (Lembaga Pengembangan Kinerja Dosen, 2026)
Bullying is a common occurrence in schools and public settings, often affecting children. However, this issue often goes unnoticed because it is considered commonplace, despite the significant impact it can have on victims. This study aims to determine the impact of bullying on a child's personality and educational process. The impact of bullying on children who are victims of bullying is that victims experience physical and non-physical violence. These include frequent social isolation, a lack of close friends, poor relationships with parents, and declining mental health. The worst impact for children who are victims of bullying is depression and even suicide. This can lead to prolonged trauma for children who are victims of bullying. Furthermore, a child who is a victim of bullying will also experience learning and academic difficulties. One action that can be taken for a child who is a perpetrator or victim of bullying is to provide affection, trust, involve them in positive activities, and educate them about the negative impacts of bullying. Therefore, collaboration between schools, teachers, and parents is needed to address bullying against children.